Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0167803
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Characteristics of Erythromycin Resistant Streptococcus pneumoniae with Preferred PCV Usage in Iran

Abstract: Amongst 100 Streptococcus pneumoniae isolated from clinical cases and nasopharynx of healthy individuals, 60 erythromycin resistant strains were isolated and characterized using MLST, PFGE, transposon analysis and Quellung reaction. Most of the S. pneumoniae erythromycin resistant (80%) were found to be attributable to the ermB-edncoded ribosome methylase activity which differs from the dominant mechanism of macrolide resistance seen in North America.The most predominant transposons were; Tn1545/6003 (27%), Tn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
(33 reference statements)
3
23
0
Order By: Relevance
“…In our study, the major mechanism conferring resistance to macrolide antibiotics was the constitutive phenotype (43%) mostly correlated with the ermB resistance gene (52%). The findings of the current study were in agreement with previous reports from our country, in which ermB (50%) was the most frequent genetic determinant among ERSP (20). In a study in Turkey, Kittana et al reported that the majority of the ERSP isolates (88.2%) had a constitutive phenotype and 89.1 and 50% of the ERSP isolates harbored ermB and mefE genes, respectively [22].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the major mechanism conferring resistance to macrolide antibiotics was the constitutive phenotype (43%) mostly correlated with the ermB resistance gene (52%). The findings of the current study were in agreement with previous reports from our country, in which ermB (50%) was the most frequent genetic determinant among ERSP (20). In a study in Turkey, Kittana et al reported that the majority of the ERSP isolates (88.2%) had a constitutive phenotype and 89.1 and 50% of the ERSP isolates harbored ermB and mefE genes, respectively [22].…”
Section: Resultssupporting
confidence: 93%
“…[19]. In another study, conducted by Talebi et al in 2016, the percentages of resistance to tetracycline and penicillin in the erythromycin resistant S. pneumoniae isolates (ERSP) were 85 and 28% [20]. High resistance rates to erythromycin (80.2%), tetracycline (91.2%) and penicillin (47.3%) were reported from China [21].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…8 The increase of multi-drug resistant (MDR) S. pneumoniae has been reported in the Middle Eastern countries, which is becoming a serious problem around the world. 9 High antibiotic resistances have been reported in some serotypes, such as 23F, 19A, 19F, and 14. 10 Usually, pneumococcal vaccines target several serotypes belonging to antimicrobial-non-susceptible clones i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent discoveries of methyltransferases have also identified target modification without genetic modification as a means of antibiotic resistance. For example, the erythromycin ribosome methylase (erm) family of genes alter the active site of 16S rRNA through methylation, effectively protecting the site from antibiotic disruption (Talebi et al, 2016). The erm genes are often carried on plasmids, making for a clinically dangerous mechanism of gene transfer.…”
Section: Antibiotic Mechanisms Of Action and Collateral Sensitivitymentioning
confidence: 99%